Weakened overturning and tide control the properties of Oyashio Intermediate Water, a key water mass in the North Pacific - Vigan Mensah (Nature Portfolio, 2021)
Abstract The western subarctic Pacific exhibits major biological productivity fed by the Oyashio Current and its two source waters: Western Subarctic Water, which supplies nutrients from the subarctic Pacific, and cold Okhotsk Sea Intermediate Water (OSIW), which supplies iron from the Sea of Okhotsk. We created seasonal climatologies of water properties to understand how the long-term trend (~ 50 years) and 18.6-year tidal cycle affect the Oyashio Intermediate Water (OYW). We found that over the trend, decreased OSIW outflow due to weakening of North Pacific overturning modifies OYW in winter. Meanwhile, OSIW outflow increases (decreases) in strong (weak) tide years. We predict that the opposite effects of the trend and strong tide will lead to stagnation of OYW properties until the mid-2020s, followed by accelerated warming until the mid-2030s (weak tide). A predicted 1 °C increase in OYW temperature and 50% decrease in OSIW content between 1960 and 2040 potentially have significant impact on biological productivity and carbon drawdown in the North Pacific.